The centenary of Hereditas - almost a fairytale - Shi, Yongyong; Baumgartner, Stefan (Hereditas, 2020)
This is the Editorial for a series of articles illuminating the history and success story of Hereditas, one of the oldest journals in the area of genetics. For this reason, we invite you to read this special series on a journal with a distinct reputation and which can celebrate its Centenary in 2020.